Symbiotic Performance of Herbaceous Legumes in Tropical Cover Cropping Systems - Basil Ibewiro; Martin Onuh; Nteranya Sanginga; Bernard Vanlauwe; Roel Merckx (The Scientific World Journal)
Increasing use of herbaceous legumes such as mucuna (Mucuna pruriens var. utilis [Wright] Bruck) and lablab (Lablab purpureus [L.] Sweet) in the derived savannas of West Africa can be attributed to their potential to fix atmospheric nitrogen (N2). The effects of management practices on N2 fixation in mucuna and lablab were examined using 15N isotope dilution technique. Dry matter yield of both legumes at 12 weeks was two to five times more in in situ mulch (IM) than live mulch (LM) systems. Land Equivalent Ratios, however, showed 8 to 30% more efficient utilization of resources required for biomass production under LM than IM systems. Live mulching reduced nodule numbers in the legumes by one third compared to values in the IM systems. Similarly, nodule mass was reduced by 34 to 58% under LM compared to the IM systems. The proportion of fixed N2 in the legumes was 18% higher in LM than IM systems. Except for inoculated mucuna, the amounts of N fixed by both legumes were greater in IM than LM systems. Rhizobia inoculation of the legumes did not significantly increase N2 fixation compared to uninoculated plots. Application of N fertilizer reduced N2 fixed in the legumes by 36 to 51% compared to inoculated or uninoculated systems. The implications of cover cropping, N fertilization, and rhizobia inoculation on N contributions of legumes into tropical low-input systems were discussed.